TAFSIR DAN PEMBAHARUAN PEMIKIRAN ISLAM DI INDONESIA ERA KEMERDEKAAN: (STUDI ANALISIS KITAB TAFSIR AL-FURQAN KARYA AHMAD HASSAN) - Ahmad Bayu Setiawan (Sekolah Tinggi Agama Islam Sadra, 2023)
The conflict dynamics of revivalist and traditionalist Islamic groups always colorize development of ideological contest of religious live in Indonesia. One of the important episodes of this conflict dynamic occurred in the era of independence. Through this paper, the author is interested in portraying episodes of Islamic Revivalist dynamics in the independence era through the thoughts and works of influential revivalist scholars, namely Ahmad Hassan. This study aims to reveal the form of mediation of Ahmad Hassan's Islamic renewal in his book of tafsir Al-Furqan. The author uses a descriptive method of analysis with literature study techniques in reviewing the interpretation of Al-Furqan as the main object of research. The results showed that in mediating Ahmad Hassan's Islamic renewal, Kitab tafsir Al-Furqan accommodates and mediates Islamic renewal in two ways, namely formative and substantive ways. Formative way of mediation is indicated through the form of tafsir Al-Furqan as a literal and meaningful translation of tafsir. Critically, this form of translation aimed to make Al-Furqan accessible for Indonesian people at that time when they haven’t had proper understanding on Arabic literacy so that people could understand and refer to the meaning of the Qur'an directly. This is in line with Ahmad Hassan's renewal though about the Qur'an and hadith as the main sources of muslims. As for the substantive ways of mediation, tafsir Al-Furqan contains and expresses the thoughts of Ahmad Hassan's renewal as a substance in interpreting the verses of the Qur'an.